The flexibility and convenience of using a standard orthopaedic table in peri-articular knee fractures: Allowing ligamentotaxis and improving imaging accessibility - Zaid AL-Ani; Shaival S. Dalal; Amit Chandratreya; Khalid Sharif; Sarvpreet Singh (Chinese Journal of Traumatology, 2022)
Tibial plateau and distal femoral fractures are common injuries presenting a significant operative challenge. Complexity of the fracture often needs multi-planar surgical access. A combined two-staged procedure is frequently suggested both in supine and prone position to address this issue. However, this will significantly increase the operative time and eventually impact the outcome, in addition to the complications associated with prone positioning. In this study we used a standard orthopaedic table to position these patients in order to grant access to the postro-medial and a postro-lateral structures while the patient stays in supine setup, at the same time, giving the flexibility to change the alignment from valgus to varus and vice versa. This facilitates fracture reduction while addressing the anatomical structure of the knee. A further advantage is the unobstructed imaging access throughout the surgical fixation. This facilitates the reduction in operative time hence leading to a better outcome in these difficult fractures. We tested this positioning technique in more than 40 patients over a 4-year period at two different centres in the United Kingdome. We found that this approach is safe, reproducible and relatively easy to set up in the two centres.